WOMEN’S LANGUAGE FEATURES ON UTTERANCES OF CHARLIE’S ANGELS MOVIE - Sekarayu Nuringtyas, Ais Navila (Universitas Muhammadiyah Surakarta, 2022)
The study entitled Women's Language Features on Utterances of Charlie's Angels Movie seeks to examine women's language features and the reasons of using the features by the three main women character. The data was taken from the utterances of the Charlie's Angels (2019) movie. The researchers used Lakoff's hypothesis to investigate women's language features. Lakoff (1975) suggested ten language features for women, but this analysis only found nine features in this movie, namely lexical hedges or fillers, intensifiers, tag question, emphatic stress, rising intonation on declaratives, avoidance of strong swear words, super polite forms, empty adjectives, and hypercorrect grammar. The findings indicated that intensifiers appeared to be the most prominent attribute utilized among the three main women’s characters in the movie (45.4%), and the least feature is the tag question (1.81%). Regarding the reasons for using Women's Language Features as the most frequent feature in this movie, the feature occurs when the speakers try to give a strong opinion or persuade the other person. Furthermore, the reason of tag question occurs in this movie because to convenience the hearer about what the speaker’s said.